Inverse National Trends of Laser Interstitial Thermal Therapy (LITT) and Open Surgical Procedures for Refractory Epilepsy: A Nationwide Inpatient Sample Based Propensity Score Matched Analysis. (16th November 2020) - Sharma, Mayur; Ball, Tyler; Alhourani, Ahmad; Ugiliweneza, Beatrice; Wang, Dengzhi; Boakye, Maxwell; Neimat, Joseph S
Abstract: INTRODUCTION: Surgery for medical refractory epilepsy (RE) is an underutilized treatment modality, despite its efficacy. Laser interstitial thermal therapy (LITT) is a minimally invasive, which is increasingly being utilized for a variety of brain lesions and offers comparable seizure outcomes. METHODS: Data was extracted using the ICD-9/10 codes from the Nationwide Inpatient Sample (NIS, 2012–2016) in this retrospective study. Patients with a primary diagnosis of RE who underwent either open surgeries (lobectomy, partial lobectomy and amygdalohippocampectomy) or LITT were included. Patient demographics, complications, length of hospital stay (LOS), discharge disposition and index-hospitalization costs were analyzed. Propensity score matching (PSM) was used to analyze outcomes. RESULTS: A cohort of 128, 525 in-hospitalized patients with RE was included and 5.5% (n = 7045) of these patients underwent either open surgical procedures (94.3%) or LITT (5.7%). LITT is increasingly being performed at a rate of 1.09 per 1000 epilepsy admissions/year while open surgical procedures are decreasing at a rate of 10.4/1000 cases/year. The majority of procedures was elective (92%) and was performed at large bed size (86%) hospitals. All LITT procedures were performed at teaching facilities and the majority was performed in south (37%) or West (30%) regions. Median LOS was 1 day for LITT cohort and 4 days for the open cohort. Index hospitalization charges were significantly lower following LITT compared to open procedures ((LITT: $ 108, 332; open: $ 124, 012, P  < .0001). LITT was associated with shorter median LOS, high likelihood of discharge to home and low median index hospitalization charges compared to open procedures for RE on PSM analysis. CONCLUSION: LITT is increasingly being performed in favor of open procedures. LITT is associated with a shorter LOS, a higher likelihood of being discharged home and lower index-hospitalization charges compared to open procedures. LITT is a safe treatment modality in carefully selected patients with RE and offers an opportunity to increase the utilization of surgical treatment in patients who may be opposed to open surgery or have contraindications that preclude open surgery.